The Duke of Alba: The Ideal Enemy - Horst, Daniel R. (My University, 2014)
This article I will show how the image Fernando Álvarez de Toledo, III Duke of Alba (1507-1582) portrayed by Netherlandish propagandists during the Dutch Revolt corresponds with older existing Netherlandish stereotypes of the Spanish people in general. The duke of Alva is widely criticized for his Pride, a sin which most clearly visible in the statue of himself which the duke erected in Antwerp in 1571. The connection between Alva and the vice of Pride is used over and over again in Dutch anti-Spanish propaganda during Alva’s reign in the Netherlands but also remains a popular theme well into the seventeenth, eighteenth and even nineteenth centuries. I will illustrate this popularity with some examples of less well-known Dutch prints from these periods dealing with the duke of Alva. Finally I will show how the duke of Alva’s name still lives on in modern day Dutch language., En este trabajo voy a presentar cómo la imagen de Fernando Álvarez de Toledo, III Duke of Alba (1507-1582) ofrecida por los propagandistas neerlandeses durante la Revuelta holandesa se corresponde con antiguos estereotipos holandeses sobre los españoles en general. El duque de Alba es ampliamente criticado por su orgullo, un pecado más claramente visible en la estatua de su figura erigida en Antwerp en 1571. La conexión entre Alba y el vicio de orgullo se usa reiteradamente en la propaganda holandesa anti-española durante el gobierno del duque de Alba en las Provincias Unidas pero igualmente permanece como un tema popular con algunos ejemplos de textos menos conocidos de este período que tratan sobre el duque de Alba. Finalmente mostraré cómo el nombre del duque de Alba vive todavía en la lengua holandesa.
Keywords: Fernando Álvarez de Toledo (Duke of Alba); Visual propaganda; Dutch Revolt; Eighty Years’ War; Spaniards stereotypes; Fernando Álvarez de Toledo (Duque de Alba); propaganda visual; Revuelta holandesa; Guerra de Ochenta Años; estereotipos españoles